Farm-level Losses and Grower Willingness to Try Management Strategies for Swede Midge in Vegetable Crops - Elisabeth A. Hodgdon; Andrea E.M. Campbell; David S. Conner; Christine A. Hoepting; Andrew K. Galimberti; Yolanda H. Chen (HortTechnology, 2022)
Since its introduction to North America in the 1990s, the invasive swede midge (Contarinia nasturtii) has become an important pest of cruciferous (Brassicaceae) vegetables in the northeast and Great Lakes regions of the United States and the Canadian provinces of Québec and Ontario. Swede midge reduces yield in cruciferous vegetables through larval feeding that distorts growth. Overlapping generations, cryptic larval feeding, and lack of effective biopesticides pose challenges for managing swede midge effectively using current tools. In 2018, we distributed an online survey for commercial vegetable growers in the United States and Canada to measure farm-level economic impacts of swede midge and grower perspectives on new management strategies for this pest. Growers reported losing $3808 US ($4890 Canadian) on average per acre per year due to swede midge–related vegetable crop losses. Both organic and conventional growers expressed an interest in paying more for nonchemical swede midge management vs. insecticides and were interested in trying new management strategies, particularly biological control.